Beyond the Mosque Walls: AI, Social Media, and the Future of Digital Islamic Education for Global Religious Harmony - Elihami Elihami (Al-Mirah: Jurnal Pendidikan Islam, 2026)
The rapid advancement of Artificial Intelligence (AI) and social media has transformed the landscape of education, communication, and religious engagement in contemporary society. This study explores the role of digital Islamic education in fostering global religious harmony beyond traditional institutional boundaries. The research examines how AI-powered learning platforms, social media mediation, and digital literacy contribute to the dissemination of inclusive Islamic values, intercultural dialogue, and peaceful coexistence in multicultural societies. Using a qualitative literature review approach, this study analyzes recent developments in digital pedagogy, AI integration, and online religious communication within Islamic education. The findings reveal that AI and social media can serve as transformative tools for strengthening religious moderation, promoting ethical digital behavior, and expanding access to Islamic learning across diverse communities. However, the study also identifies challenges such as misinformation, online radicalization, algorithmic bias, and the commercialization of religious content. Therefore, the future of digital Islamic education requires collaborative strategies involving educators, policymakers, religious leaders, and technology developers to ensure that digital transformation supports peace, tolerance, and global human solidarity. This study contributes to the growing discourse on the intersection of Islamic education, digital technology, and social harmony in the era of Society 5.0.